The class A scavenger receptor MARCO is the major phagocytic receptor for Clostridium sordellii expressed by human decidual macrophages - Thelen, Tennille (J Immunol, 2010)
Clostridium sordellii is an emerging pathogen associated with highly-lethal female reproductive tract infections following childbirth, abortion, or cervical instrumentation. Gaps in our understanding of the pathogenesis of C. sordellii infections present major challenges to the development of better preventive and therapeutic strategies against this problem. We sought to determine the mechanisms whereby uterine decidual macrophages phagocytose this bacterium and tested the hypothesis that human decidual macrophages utilize class A scavenger receptors (CASR) to internalize unopsonized C. sordellii. In vitro phagocytosis assays with human decidual macrophages incubated with pharmacological inhibitors of CASRs (fucoidan, polyinosinic acid, and dextran sulfate) revealed a role for these receptors in C. sordellii phagocytosis. Soluble MARCO receptor prevented C. sordellii internalization, suggesting that MARCO is an important CASR in decidual macrophage phagocytosis of this microbe. Peritoneal macrophages from MARCO-deficient mice, but not wild-type or SR-AI/II-deficient mice, showed impaired C. sordellii phagocytosis. MARCO-null mice were more susceptible to death from C. sordellii uterine infection than wild-type mice and exhibited impaired clearance of this bacterium from the infected uterus. Thus, MARCO is an important phagocytic receptor utilized by human and mouse macrophages to clear C. sordellii from the infected uterus.